Methods to quantify calcium carbonate precipitation in small scale - Nur Insyirah Mazlan (Nanyang Technological University, 2021)
Bio cement is a new process used to aid the construction industry in strengthening the concrete material. Cracks on concrete are inevitable in the long run. Especially when the concrete material is exposed to extreme load and weathering. Bio cement has a self-healing property that could prevent worsening of cracks. If cracks are not well maintained, it can cause catastrophic accidents. The process of bio cement follows MICP (Microbially induced calcium carbonate precipitation). In this process, addition of urea and calcium ion on bacteria results in the formation of calcium carbonate and ammonium ion. In this study the bacteria used is Sporosarcina Pasteurii (DSM33). It has a high urease activity which allow the crystallization of calcium carbonate to occur in between cracks of cement. On top of that, to quickly and indirect method identifying the urease activity in the bio cement is quantify the reactants and product of calcium carbonate reaction. In this case, quantifying ammonium, and calcium ion. This study will be using Nessler reagent and chromogenic reagent respectively. These two reagents allow the reaction with ion to precipitate a certain colour. By colorimetric method, the absorbance can be measured using a microplate reader. By developing a standard concentration against absorbance linear graph for both ions, it can be checked against the absorbance for bio cement effluent. As the solution of urea, calcium chloride and DSM33 is injected at different interval, the effluent can be obtained and measure for absorbance. As a result, the small-scale standard serves as a reference to identify the number of ions present in the effluent.